2022
DOI: 10.1016/j.lanwpc.2021.100372
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between plant-based dietary pattern and air pollution on cognitive function: a prospective cohort analysis of Chinese older adults

Abstract: Background Air pollution is a risk factor for poor cognitive function, while a plant-based dietary pattern is associated with better cognitive function. We aimed to explore their interaction with cognitive function among older adults.Methods We used a prospective cohort of old individuals, including 6525 participants of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), aged 65-110 years and with normal cognition at baseline. Air pollution measurement was derived using satellite-derived annual average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…A Mediterranean diet reduced cardiovascular disease mortality risk related to long-term exposure to air pollutants in a large prospective US cohort ( Lim et al, 2019 ). A prospective cohort study of Chinese older adults reported that a plant-based dietary pattern mitigated the adverse effects of air pollution on cognitive function ( Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Mediterranean diet reduced cardiovascular disease mortality risk related to long-term exposure to air pollutants in a large prospective US cohort ( Lim et al, 2019 ). A prospective cohort study of Chinese older adults reported that a plant-based dietary pattern mitigated the adverse effects of air pollution on cognitive function ( Zhu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a healthy diet might be beneficial to hearing impairment by protecting microvascular and macrovascular damage to cochlear blood flow ( Appel et al, 2006 ; Fung et al, 2008 ), providing the essential nutrients for an adequate cochlear blood supply ( Yevenes-Briones et al, 2021 ), and reducing inflammation ( Neale et al, 2016 ). According to previous research, dietary patterns could modify the relationship between air pollution and health-related outcomes, such as cardiovascular disease mortality risk ( Lim et al, 2019 ) and cognitive function ( Zhu et al, 2022 ). However, the moderating effect of a healthy diet on the link between hearing impairment and air pollution has not been investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…The MMSE contains a total of 30 items that assess orientation, registration, attention and calculation, recall, and language, with a score range from zero to 30 [ 36 , 37 ]. Use of the MMSE in the CLHLS is well-documented as both reliable and valid [ 22 , 35 , 38 , 39 , 40 , 41 ]. Since MMSE scores might be influenced by education level [ 40 ], participants were defined as cognitively impaired following education-based MMSE cutoff points.…”
Section: Methodsmentioning
confidence: 99%
“…Use of the MMSE in the CLHLS is well-documented as both reliable and valid [ 22 , 35 , 38 , 39 , 40 , 41 ]. Since MMSE scores might be influenced by education level [ 40 ], participants were defined as cognitively impaired following education-based MMSE cutoff points. Specifically, we used the MMSE scores of 18, 20, and 24 as the cut-off points for subjects with no formal education, only a primary school education (1–6 years), and a middle-school or higher education (>6 years), respectively [ 32 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation